Method for preparing high-performance surface modified titanium filter by recycling titanium waste
By using other external titanium to prepare porous titanium filters and undergoing surface modification of nitrogen or methane gas, the existing titanium tetrachloride filters have been solved, and the filtration accuracy of high-performance and low-cost filtering effect is achieved.
Patent Information
- Application Number
- CN202411971359.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2044-12-30
AI Technical Summary
The existing titanium tetrachloride filters have short service life, are easy to perforate, easily broken, have insufficient filtration accuracy, complex process flow, easy to block pores, uneven pore distribution, high temperature resistance, poor corrosion resistance, high preparation cost, and poor filtration efficiency.
Isotropic titanium filters are prepared by hydrogenation treatment, high-energy ball milling, cold isostatic pressure and vacuum sintering, and surface modification of nitrogen or methane gas is performed on the surface to generate a TiC or TiN reinforced coating.
The preparation of high-performance surface-modified titanium filters is realized, which extends service life, improves filtration accuracy and efficiency, reduces production costs, and promotes the recycling and utilization of titanium resources.
Smart Images

Figure CN119859757A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of filter preparation, in particular to a method for preparing a high-performance surface-modified titanium filter by recycling titanium waste. Background Art
[0002] Titanium (Ti) and its alloys have high specific strength, good corrosion resistance, excellent high temperature resistance and biocompatibility. They are not only widely used in aerospace, defense equipment, marine engineering, chemical industry and medical equipment, but also perform well in filtration applications under extreme environments. They are considered to be ideal materials for high-performance filters.
[0003] Titanium tetrachloride is the basic raw material for preparing titanium sponge, but because the impurity content in the rich material used for chlorination is high, this causes a large amount of solid impurities in the prepared titanium tetrachloride. Since these solid phases will seriously affect the stable operation of the refining system and the quality of the refined titanium tetrachloride product, higher requirements are placed on the efficiency of titanium tetrachloride purification. In the past, filters such as stainless steel and ceramics were used for filtration, which had problems such as short filter life, easy perforation, and breakage. Therefore, at this stage, factories usually use metal titanium filters for purification. However, TiCl4 has certain corrosiveness, and metal titanium filters will still have problems such as corrosion, low yield, and further improvement of service life during use. In addition, the use of electrolytic titanium powder material as the metal titanium filter material makes the metal titanium filter very expensive, which seriously restricts the development of titanium tetrachloride filtration technology. Therefore, it is necessary to regulate the intrinsic properties of the metal titanium filter to improve its corrosion resistance and increase the service life of the metal titanium filter.
[0004] In addition, substandard titanium is a product that cannot meet the national quality standards for sponge titanium due to its quality, morphology and particle size during the production process of sponge titanium. Currently, substandard titanium is mainly used as an additive for steelmaking, a grain refiner for aluminum processing, a raw material for smelting titanium-iron alloys, titanium casting, and titanium powder metallurgy. However, these uses have failed to fully utilize the value of substandard titanium, and it is urgent to develop a preparation technology for efficient recycling of substandard titanium to achieve high-value utilization of titanium resources.
[0005] Therefore, there is an urgent need for a low-cost, high-yield, near-final-form preparation method that uses off-grade titanium, sponge titanium or titanium waste as raw materials or additives for filters, which can significantly reduce the manufacturing cost of titanium filter elements, improve the material properties of titanium filters through coating, and realize the recycling of titanium waste to meet the needs of high-efficiency and low-cost purification of titanium tetrachloride and high-value utilization of off-grade titanium recovery.
[0006] Chinese patent CN108251789A discloses a method for in-situ preparation of TiCN coating on titanium alloy surface, which comprises applying vaseline paste on the surface of titanium alloy workpiece after mechanical cleaning, then laser irradiating under nitrogen atmosphere protection, and finally cleaning and drying. Although the prepared TiCN coating can improve heat dissipation, wear resistance, local repairability and corrosion resistance, it will block the pores if applied to porous structures.
[0007] Chinese patent CN104141063A discloses a method for preparing an in-situ synthesized titanium carbide reinforced titanium-based porous material, which adopts powder metallurgy pore-forming agent technology and uses urea, carbon powder and titanium powder to in-situ synthesize titanium carbide reinforced porous titanium-based composite materials through ingredient mixing, pressing and sintering treatment steps; although the mechanical properties, high temperature properties and corrosion resistance are enhanced, urea as a pore-forming agent will make the porosity and pore size uniformity of the prepared porous material insufficient, affecting the filtration accuracy and filtration efficiency when the porous material is used as a filter.
[0008] Chinese patent CN107287464A discloses a method for preparing a titanium-based porous composite material containing nano-TiN ceramics. The method adopts powder metallurgy pore-forming agent technology. A composite powder preform containing nano-TiN ceramic particles is prepared by introducing high-purity nitrogen at a certain pressure during ball milling of titanium powder. A certain amount of anhydrous ethanol is added as a mixing agent and a binder, and the mixture is uniformly mixed with short rod-shaped urea, and the green body is pressed, low-temperature vacuum sintered, and high-temperature solid-phase sintered to prepare the titanium-based porous composite material. Not only is the preparation process complicated, but the preparation amount of nano-titanium nitride particles and their distribution in the composite powder are difficult to be effectively controlled. The defects of urea as a pore-forming agent have not been resolved, and the filtration performance of the prepared porous material is poor. Summary of the invention
[0009] In order to solve the technical defects of the titanium filter currently used for titanium tetrachloride filtration in the prior art, such as short service life, easy perforation, easy breakage, insufficient filtration accuracy, complex process flow, easy clogging of pores, uneven pore distribution, high temperature resistance, poor corrosion resistance, high preparation cost, and poor filtration efficiency, although it can be alleviated by preparing a coating, there will be large urea loss and poor pore opening effect during the preparation of the coating, the nano-TiN ceramic particles and the titanium alloy matrix are not tightly combined, the nano-TiN particles are unevenly distributed, it is difficult to simultaneously control the size, distribution and shape of the pores, and the interaction between the pores and the particles, high temperature may cause the interface bonding force to be further weakened, or adverse chemical reactions may occur between the particles and the matrix. The present invention proposes a method for preparing a high-performance surface-modified titanium filter by recycling titanium waste that can solve the above-mentioned problems. The technical scheme is as follows:
[0010] A method for recycling titanium waste to prepare a high-performance surface-modified titanium filter, the method for recycling titanium waste to prepare a high-performance surface-modified titanium filter comprises the following steps:
[0011] S1. hydrogenation of titanium raw material: hydrogenation treatment is performed on titanium raw material block by using hydrogenation furnace to obtain easily breakable hydrogenated titanium block;
[0012] S2. Preparation of micron-sized titanium hydride powder: The easily broken titanium hydride block in S1 is placed in a ball mill filled with high-purity argon gas for high-energy ball milling, and a pore-forming agent is added during ball milling to obtain micron-sized titanium hydride powder;
[0013] S3. Preparation of cold forming mold for porous titanium filter: a tubular or square tubular soft sleeve is made of polyurethane or silicone, with a stainless steel core rod in the middle of the soft sleeve, which is fixed by a polyurethane or silicone plug matched with the tenon of the upper and lower ports of the soft sleeve, and a porous stainless steel bushing is matched with the outside of the polyurethane or silicone soft sleeve, the length of the bushing is consistent with the length of the soft sleeve, and the diameter of the bushing is larger than the diameter of the soft sleeve, and the cold forming mold is composed of the soft sleeve, the core rod, the plug and the bushing;
[0014] S4, preparation of porous titanium filter compact: loading the micron-grade titanium hydride powder of S2 into the tubular or square tubular soft package in S3, and performing sealing and assembly treatment; then placing the forming mold filled with the powder into a cold isostatic press for cold isostatic pressing, demolding and taking out, to obtain a tubular or square tubular porous titanium filter compact;
[0015] S5. Preparation of porous titanium filter: placing the S4 tubular or square tubular titanium filter compact into a vacuum sintering furnace, evacuating the vacuum furnace and heating and sintering the compact to obtain a porous titanium filter;
[0016] S6. Surface modification of porous titanium filter: nitrogen or methane gas is passed into the S5 porous filter for surface modification to obtain a high-performance porous titanium filter with a porous coating on the surface.
[0017] Optionally, the temperature of hydrogenation treatment in S1 is 300-600°C, the holding time is 1-4h, the hydrogen content in the easily broken hydrogenated titanium block is 2-3.2wt.%, and the titanium raw material block is off-grade titanium, sponge titanium or other titanium waste with no oil on the surface.
[0018] Optionally, the pore-forming agent in S2 is NaCl, KCl or CaCl2 salt, and the added amount is 1-5wt.%; the ball-to-material ratio of high-energy ball milling is 5:1-10:1, the ball milling speed is 300-600rpm, the grinding balls are stainless steel balls with a diameter of 6-10mm, the ball milling time is 2-4h, the particle size of the micron-sized titanium hydride powder is 50-200 mesh, and the shape is irregular block.
[0019] Optionally, in S3, the total length of the soft sleeve is 5-200cm and the thickness is 5-25mm. The lower end of the soft sleeve structure is a whole mold and cannot be opened, while the upper end is a split mold and is partially opened through serrated or corrugated meshing. The length of the upper end is 1 / 2-3 / 4 of the total length of the sleeve; the stainless steel bushing is a left and right split mold structure, fixed with a throat clamp or a buckle, and the bushing thickness is 1-3mm; the core rod taper is 1-3°, and the bushing diameter is 2-8mm larger than the soft sleeve diameter; the hole diameter of the porous stainless steel bushing is 3-20mm, and the hole area is 50-80% of the outer surface area of the bushing.
[0020] Optionally, the pressing pressure of the cold isostatic pressing in S4 is 80-200 MPa, the pressure is maintained for 60-240 s, the wall thickness of the tubular or square tubular titanium filter blank is 10-20 mm, and the porosity is 30-55%.
[0021] Optionally, the vacuum sintering temperature in S5 is 950-1200°C and the vacuum degree is 10 -2 Pa, sintering time is 1-4h.
[0022] Optionally, the high performance porous titanium filter in S5 has a porosity of 30-60%, a pore size of 10-100 μm, a hydrogen content of ≤0.03wt.%, and a compressive strength of ≥150MPa.
[0023] Optionally, the temperature of the surface modification treatment in S6 is 750-1000° C., and the holding time is 1-2 h.
[0024] Optionally, the inner and outer walls of the porous titanium filter with a high-performance surface porous coating in S6 are both porous coatings of TiN or TiC, with a coating thickness of 1-3 mm, a porosity of 30-60%, a pore size of 10-100 μm, a hydrogen content of ≤0.03wt.%, and a compressive strength of ≥200 MPa.
[0025] Technical principle of the present invention:
[0026] In order to solve the defects of existing titanium tetrachloride filtration filters such as short service life, easy perforation, easy breakage, insufficient filtration accuracy, and high production cost, the present invention proposes to use off-grade titanium as the main raw material and combine hydrogenation crushing, cold isostatic pressing and vacuum sintering technologies to prepare a high-performance filter, thereby realizing high-value recovery and utilization of off-grade titanium.
[0027] The raw material titanium of the present invention is not limited to off-grade titanium, and sponge titanium or other titanium waste materials without oil stains on the surface, such as titanium chips, scraps, etc., can be used as the preparation raw material. The raw material cost is low, the industrial applicability is strong, the process is simple, the process is short, and it is not only suitable for titanium tetrachloride filtration, but also suitable for other industrial product filtration, and has good technical universality.
[0028] The soft bag structure, core rod taper design, core rod fixing method and stainless steel bushing structure designed in the present invention are obtained through a large number of experimental optimization and verification, and are combined with the characteristics of titanium alloy powder, forming problems, demolding difficulty and filter structure and quality, and are matched with deformation control, shrinkage rate, porosity, coating thickness and other parameters in the cold forming process of titanium alloy filter. They cannot be inferred based on conventional experimental operations.
[0029] In order to ensure the integrity and forming quality of the direct-formed filter structure, the present invention designs a soft package structure, the lower end is a whole mold that cannot be opened, and the upper end is a split mold that can be partially opened, through serrated or corrugated meshing, the length of the upper end is 1 / 2-3 / 4 of the total length of the package, which can ensure that the formed filter blank is easy to demold, the blank structure is complete, and there is no damage, missing corners, cracks and other problems. The lower end cannot be opened, which ensures the accuracy of the mold closing, and can avoid problems such as inaccurate mold closing positioning and poor surface quality of the blank caused by the excessive length of the package.
[0030] In order to directly form a hollow filter, the present invention designs an intermediate core rod structure, and the core rod is fixed by a plug matched with the upper and lower port tenons of the soft sleeve, which not only ensures that the core rod will not move during the powder filling process, so that the powder filling is uniform and the wall thickness of the blank is consistent, but also ensures the straightness of the hollow structure of the filter, and in order to facilitate demoulding without damaging the internal structure of the blank, the core rod is designed with a taper of 1-3°. After the blank is formed, the taper design allows the core rod to be directly removed, which is simple and convenient to operate, and the internal structure of the blank is complete without defects. The taper angle design is obtained through a large number of experimental verifications. If it is too large, there will be problems such as uneven stress, inability to form, or cracking of the pressed blank.
[0031] In order to ensure the quality of the outer surface of the filter blank, the present invention designs a porous stainless steel bushing structure, the diameter of the bushing hole is 3-20mm, the hole area is 50-80% of the outer surface area of the bushing, and the thickness is 1-3mm, which not only ensures the shape structure of the soft package, so that the tall and long filter blank structure does not deform, does not have problems such as bending and warping, but also ensures the meshing stability of the upper end opening soft package, avoiding defects such as bumps at the opening gap. At the same time, the porous structure design does not affect the transmission of liquid pressure to the soft package, ensuring the consistency of the blank density. In addition, the left and right split mold structure of the bushing makes the demoulding operation simple.
[0032] The present invention directly simplifies the process of preparing titanium powder, proposes to use incompletely hydrogenated titanium hydride as raw material to prepare a porous titanium filter, during the sintering process, the titanium hydride will undergo a dehydrogenation reaction to achieve dehydrogenation and sintering integration, and the high-temperature hydrogen escaped plays a role in pore formation. After sintering, the hydrogen content is ≤0.03wt.%, shortening the production process and reducing the production cost.
[0033] The hydrogenated powder used in the present invention has a particle size of 50-200 meshes, which avoids the problem that when the powder particle size is small, the relative density of the pressed green sheet is large and it is difficult to ensure the porosity of the filter, and also avoids the problems that when the powder particle size is large, the filter strength is low, slag is easy to fall off, and the service life is short.
[0034] During the preparation process of the present invention, the hydrogen content of the titanium hydride block is ≥2wt.% and ≤3.2wt.%, which is obtained through a large number of experimental verifications and optimizations, and cannot be obtained through conventional experimental calculations. The lower limit of the hydrogen content of 2wt.% ensures that the titanium hydride block can be easily broken during high-energy ball milling, and the upper limit of 3.2wt.% ensures the stability of the pressed green sheet structure during the pressing process, and is not easy to be crushed, and avoids the problem that the hydrogen content is too high, resulting in too much dehydrogenation during the sintering process, causing the integrity of the filter structure to be destroyed, cracks, etc., and incomplete hydrogenation reduces production costs and improves production efficiency. It is worth noting that the present invention directly simplifies the process of preparing titanium powder, and proposes to use incompletely hydrogenated titanium hydride as a raw material to prepare a porous titanium filter. During the sintering process, titanium hydride will undergo a dehydrogenation reaction to achieve dehydrogenation and sintering integration, and the high-temperature escaped hydrogen plays a role in pore formation. The hydrogen content after sintering is ≤0.03wt.%, shortening the production process and reducing production costs.
[0035] The cold isostatic pressing process of the present invention ensures the yield rate of titanium filters, and by designing packages of different specifications and shapes, the requirements for filters in different application scenarios can be met; the use of off-grade titanium as a raw material to prepare the filter realizes the recycling of resources and further reduces production costs.
[0036] The present invention can generate TiC or TiN strengthening coatings in situ on the inner and outer surfaces of the porous titanium filter through nitrogen or methane gas surface treatment, which does not affect the porosity of the filter and enables the porous titanium filter to have the advantages of high wear resistance, high hardness, high corrosion resistance and the like of TiC or TiN, thereby greatly improving the service life of the filter.
[0037] The invention has low raw material cost, simple preparation process, short process, strong industrial applicability, and recycles titanium resources, thus realizing the sustainable development of titanium resources. The filter prepared by the invention is not only applicable to the field of titanium tetrachloride filtration, but also to the filtration of other industrial products, especially the filtration of products in extreme environments, and has good technical universality.
[0038] Compared with the prior art, the above technical solution has at least the following beneficial effects:
[0039] The above scheme proposes a method for recycling titanium waste to prepare a high-performance surface-modified titanium filter, which can solve the problems of the titanium filter currently used in titanium tetrachloride in the prior art, such as short service life, insufficient filtration accuracy, complex process flow, easy clogging of pores, uneven pore distribution, poor high temperature resistance and corrosion resistance, high preparation cost, poor filtration efficiency, large urea loss and poor pore opening effect, insufficient tight bonding between nano-TiN ceramic particles and titanium alloy matrix, uneven distribution of nano-TiN particles, difficulty in simultaneously controlling the size, distribution and shape of pores, interaction between pores and particles, high temperature may cause further weakening of interface bonding force, or adverse chemical reactions between particles and matrix.
[0040] The present invention uses incompletely hydrogenated titanium hydride as a raw material to prepare a porous titanium filter. During the sintering process, the titanium hydride undergoes a dehydrogenation reaction to achieve dehydrogenation and sintering integration, and the hydrogen gas released at high temperature serves to form pores. After sintering, the hydrogen content is ≤0.03wt.%, shortening the production process and reducing the production cost.
[0041] The present invention adopts mold design and preparation, cold isostatic pressing process, can realize near-forming of the filter, thereby reducing the preparation cost of the filter. In particular, the specification and shape of the cold isostatic pressing package can be designed to prepare filters required by different application scenarios.
[0042] The application of the cold isostatic pressing process of the present invention also effectively improves the yield rate of the titanium filter, and the material utilization rate is ≥98%. In addition, the use of off-grade titanium as a raw material further reduces the production cost. The filter prepared by the present invention can achieve a significant improvement in the purification efficiency of titanium tetrachloride, providing a more economical and efficient solution for the recycling and production of titanium resources.
[0043] In summary, compared with other traditional methods, the method of the present invention uses off-grade titanium and other titanium waste materials with no oil on the surface, such as titanium chips, scraps, etc. as raw materials, and adopts hydrogenation crushing, cold forming, sintering, surface modification and other processes to prepare high-performance titanium filters, which have long service life, high filtration accuracy, short production process and low production cost; and solves the problems of short service life, easy perforation, easy breakage, insufficient filtration accuracy and high cost of the existing filters used to filter titanium tetrachloride. The filter preparation technology involved in the present invention has no special restrictions on the raw material composition, can meet the needs of different production environments and conditions, and has wide applicability. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0045] Figure 1 This is a process flow chart of a method for preparing a high-performance surface-modified titanium filter by recycling titanium waste according to the present invention;
[0046] Figure 2 The present invention is a method for recycling titanium waste to prepare a high-performance surface-modified titanium filter, and the soft-package sleeve and bushing structure diagram involved in the method, wherein: Figure (a) is a front view of the bushing, Figure (b) is a front view of the soft-package sleeve, and Figure (c) is a rendering of the soft-package sleeve after it is opened. DETAILED DESCRIPTION
[0047] The technical solution of the present invention is described below in conjunction with the accompanying drawings.
[0048] In the embodiments of the present invention, words such as "exemplarily" and "for example" are used to indicate examples, illustrations or explanations. Any embodiment or design described as "example" in the present invention should not be interpreted as being more preferred or more advantageous than other embodiments or designs. Specifically, the use of the word "example" is intended to present the concept in a specific way. In addition, in the embodiments of the present invention, the meaning expressed by "and / or" can be both, or it can be either of the two.
[0049] In the embodiments of the present invention, "image" and "picture" may sometimes be used interchangeably. It should be noted that when the distinction between them is not emphasized, the meanings they intend to express are consistent.
[0050] In the embodiments of the present invention, sometimes a subscript such as W1 may be written as a non-subscript such as W1. When the difference is not emphasized, the meanings to be expressed are the same.
[0051] In order to make the technical problems, technical solutions and advantages to be solved by the present invention more clear, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.
[0052] A method for recycling titanium waste to prepare a high-performance surface-modified titanium filter, the method for recycling titanium waste to prepare a high-performance surface-modified titanium filter comprises the following steps:
[0053] S1. hydrogenation of titanium raw material: hydrogenation treatment is performed on titanium raw material block by using hydrogenation furnace to obtain easily breakable hydrogenated titanium block;
[0054] S2. Preparation of micron-sized titanium hydride powder: The easily broken titanium hydride block in S1 is placed in a ball mill filled with high-purity argon gas for high-energy ball milling, and a pore-forming agent is added during ball milling to obtain micron-sized titanium hydride powder;
[0055] S3. Preparation of cold forming mold for porous titanium filter: a tubular or square tubular soft sleeve is made of polyurethane or silicone, with a stainless steel core rod in the middle of the soft sleeve, which is fixed by a polyurethane or silicone plug matched with the tenon of the upper and lower ports of the soft sleeve, and a porous stainless steel bushing is matched with the outside of the polyurethane or silicone soft sleeve, the length of the bushing is consistent with the length of the soft sleeve, and the diameter of the bushing is larger than the diameter of the soft sleeve, and the cold forming mold is composed of the soft sleeve, the core rod, the plug and the bushing;
[0056] S4, preparation of porous titanium filter compact: loading the micron-grade titanium hydride powder of S2 into the tubular or square tubular soft package in S3, and performing sealing and assembly treatment; then placing the forming mold filled with the powder into a cold isostatic press for cold isostatic pressing, demolding and taking out, to obtain a tubular or square tubular porous titanium filter compact;
[0057] S5. Preparation of porous titanium filter: placing the S4 tubular or square tubular titanium filter compact into a vacuum sintering furnace, evacuating the vacuum furnace and heating and sintering the compact to obtain a porous titanium filter;
[0058] S6. Surface modification of porous titanium filter: nitrogen or methane gas is passed into the S5 porous filter for surface modification to obtain a high-performance porous titanium filter with a porous coating on the surface.
[0059] In particular, the temperature of hydrogenation treatment in S1 is 300-600°C, the holding time is 1-4h, the hydrogen content in the easily broken hydrogenated titanium block is 2-3.2wt.%, and the titanium raw material block is off-grade titanium, sponge titanium or other titanium waste with no oil on the surface.
[0060] In particular, the pore-forming agent in S2 is NaCl, KCl or CaCl2 salt, and the added amount is 1-5wt.%; the ball-to-material ratio of the high-energy ball mill is 5:1-10:1, the ball milling speed is 300-600rpm, the grinding balls are stainless steel balls with a diameter of 6-10mm, the ball milling time is 2-4h, the particle size of the micron-sized titanium hydride powder is 50-200 mesh, and the shape is irregular blocks.
[0061] In particular, the total length of the soft sleeve in S3 is 5-200cm and the thickness is 5-25mm. The lower end of the soft sleeve structure is a whole mold and cannot be opened, while the upper end is a split mold and is partially opened through serrated or corrugated meshing. The length of the upper end is 1 / 2-3 / 4 of the total length of the sleeve; the stainless steel bushing is a left and right split mold structure, fixed with a throat clamp or a buckle, and the bushing thickness is 1-3mm; the core rod taper is 1-3°, and the bushing diameter is 2-8mm larger than the soft sleeve diameter; the hole diameter of the porous stainless steel bushing is 3-20mm, and the hole area is 50-80% of the outer surface area of the bushing.
[0062] In particular, the pressing pressure of the cold isostatic pressing in S4 is 80-200 MPa, the pressure holding time is 60-240 s, the wall thickness of the tubular or square tubular titanium filter blank is 10-20 mm, and the porosity is 30-55%.
[0063] In particular, the vacuum sintering temperature in S5 is 950-1200°C and the vacuum degree is 10 -2 Pa, sintering time is 1-4h.
[0064] In particular, the high-performance porous titanium filter in S5 has a porosity of 30-60%, a pore size of 10-100 μm, a hydrogen content of ≤0.03 wt.%, and a compressive strength of ≥150 MPa.
[0065] In particular, the temperature of the surface modification treatment in S6 is 750-1000°C, and the holding time is 1-2h.
[0066] In particular, the inner and outer walls of the porous titanium filter with high-performance porous coating on the surface of S6 are porous coatings of TiN or TiC, with a coating thickness of 1-3mm, a porosity of 30-60%, a pore size of 10-100μm, a hydrogen content of ≤0.03wt.%, and a compressive strength of ≥200MPa.
[0067] Example 1
[0068] A method for recycling titanium waste to prepare a high-performance surface-modified titanium filter, the method for recycling titanium waste to prepare a high-performance surface-modified titanium filter comprises the following steps:
[0069] S1. Hydrogenation of titanium raw materials: A 200 kg titanium block is hydrogenated in a hydrogenation furnace. The hydrogenation temperature is 300° C. The hydrogen is introduced for 2 hours. The hydrogen content in the easily broken titanium hydride block is 2.9 wt.%, and an easily broken titanium hydride block is obtained.
[0070] S2. Preparation of micron-sized titanium hydride powder: The easily broken titanium hydride block of S1 was placed in a ball milling jar filled with high-purity argon gas for high-energy ball milling. The ball-to-material ratio of the high-energy ball milling was 5:1, the ball milling speed was 300 rpm, the grinding balls were stainless steel balls with a size of 6 mm, the ball milling time was 2 h, and 2 wt.% of NaCl pore-forming agent was added during the ball milling to obtain micron-sized titanium hydride powder. The particle size of the micron-sized titanium hydride powder was 100 mesh, and the shape was irregular blocks.
[0071] S3. Preparation of cold forming mold for porous titanium filter: a tubular soft bag is made of polyurethane, with a stainless steel core rod in the middle of the soft bag, the core rod is fixed by a polyurethane plug matched with the tenon of the upper and lower ports of the soft bag, the polyurethane soft bag is matched with a porous stainless steel bushing, the length of the bushing is consistent with the length of the soft bag, and the diameter of the bushing is larger than the diameter of the soft bag, and the cold forming mold is composed of the soft bag, the core rod, the plug and the bushing;
[0072] Among them, the total length of the soft bag is 80cm, the inner diameter is 80mm, and the thickness is 10mm. The lower end of the soft bag structure is a whole mold and cannot be opened, while the upper end is a split mold and can be partially opened through serrated or corrugated meshing. The length of the upper end is 5 / 8 of the total length of the bag; the stainless steel bushing is a left and right split mold structure, fixed with a throat clamp or buckle; the core rod diameter is 58mm, the core rod taper is 2°, the bushing length is 80cm, the bushing diameter is 102mm, the bushing aperture is 5mm, and the aperture area is 60% of the total bushing area;
[0073] S4, titanium filter blank preparation: S2 micron-grade alloy powder is loaded into the tubular soft package in S3, and sealed and assembled; then the forming mold filled with powder is placed in a cold isostatic press for cold isostatic pressing, the pressing pressure of the cold isostatic pressing is 150MPa, the pressure is maintained for 180s, and the mold is removed to obtain a porous tubular titanium filter blank; the porous tubular titanium filter blank has a wall thickness of 10mm and a porosity of 40%;
[0074] S5. Preparation of porous titanium filter: Place the S4 tubular titanium filter blank into a vacuum sintering furnace, evacuate and heat to sinter. The vacuum sintering temperature is 1100°C and the vacuum degree is 10 -2 Pa, sintering time is 2h, and porous titanium filter is obtained;
[0075] The porous filter has a porosity of 40%, a pore size of 100 μm, a hydrogen content of 0.01 wt.%, and a compressive strength of 150 MPa;
[0076] S6. Surface modification of porous titanium filter: nitrogen gas was introduced into the S5 porous filter for surface modification. The surface modification temperature was 800°C, the insulation time was 1h, the TiN coating thickness was 1mm, and after cooling, a high-performance porous titanium filter with a porous coating on the surface was obtained.
[0077] The high-performance porous titanium filter with a porous coating on the surface prepared in this embodiment has a porosity of 40%, a pore size of 100 μm, a hydrogen content of ≤0.01 wt.%, and a compressive strength of 200 MPa.
[0078] Example 2
[0079] A method for recycling titanium waste to prepare a high-performance surface-modified titanium filter, the method for recycling titanium waste to prepare a high-performance surface-modified titanium filter comprises the following steps:
[0080] S1. Hydrogenation of titanium raw materials: 300 kg of titanium chips without oil on the surface were hydrogenated in a hydrogenation furnace. The temperature of the hydrogenation was 350° C. The hydrogen was introduced for 1 hour. The hydrogen content in the easily broken titanium hydride block was 3.1 wt.%, and an easily broken titanium hydride block was obtained.
[0081] S2. Preparation of micron-sized titanium hydride powder: The easily broken titanium hydride block of S1 was placed in a ball milling jar filled with high-purity argon gas for high-energy ball milling. The ball-to-material ratio of the high-energy ball milling was 8:1, the ball milling speed was 300 rpm, the grinding balls were stainless steel balls with a size of 6 mm, the ball milling time was 1 h, and 1 wt.% of NaCl pore-forming agent was added during the ball milling to obtain micron-sized titanium hydride powder. The particle size of the micron-sized titanium hydride powder was 150 meshes, and the shape was irregular blocks.
[0082] S3. Preparation of cold forming mold for porous titanium filter: a tubular soft package is made of silicone, with a stainless steel core rod in the middle of the soft package, the core rod is fixed by a silicone plug matched with the tenons of the upper and lower ports of the soft package, and a porous stainless steel bushing is matched with the outside of the silicone soft package. The length of the bushing is consistent with the length of the soft package, and the diameter of the bushing is larger than the diameter of the soft package. The cold forming mold is composed of the soft package, the core rod, the plug and the bushing;
[0083] Among them, the total length of the soft bag is 150cm, the inner diameter is 70mm, and the thickness is 15mm. The lower end of the soft bag structure is a whole mold and cannot be opened, while the upper end is a split mold and can be partially opened through serrated or corrugated meshing. The length of the upper end is 5 / 8 of the total length of the bag; the stainless steel bushing is a left and right split mold structure, fixed with a throat clamp or buckle; the core rod diameter is 38mm, the core rod taper is 1°, the bushing length is 150cm, the bushing diameter is 102mm, the bushing aperture is 10mm, and the aperture area is 80% of the total bushing area;
[0084] S4, preparation of titanium filter compact: S2 micron-grade alloy powder is loaded into the tubular soft package in S3, and sealed and assembled; then the forming mold filled with powder is placed in a cold isostatic press for cold isostatic pressing, the pressing pressure of the cold isostatic pressing is 200 MPa, the pressure is maintained for 200 seconds, and the mold is removed to obtain a porous tubular titanium filter compact; the porous tubular titanium filter compact has a wall thickness of 15 mm and a porosity of 35%;
[0085] S5. Preparation of porous titanium filter: Place the S4 tubular titanium filter compact into a vacuum sintering furnace, evacuate the vacuum and heat and sinter. The vacuum sintering temperature is 1150°C and the vacuum degree is 10 -2 Pa, sintering time is 1h, and porous titanium filter is obtained;
[0086] The porous filter has a porosity of 31%, a pore size of 80 μm, a hydrogen content of 0.01 wt.%, and a compressive strength of 160 MPa;
[0087] S6. Surface modification of porous titanium filter: methane gas was introduced into the S5 porous filter for surface modification. The surface modification temperature was 850°C, the insulation time was 1h, the TiC coating thickness was 1mm, and after cooling, a high-performance porous titanium filter with a porous coating on the surface was obtained.
[0088] The high-performance porous titanium filter with a porous coating on the surface prepared in this embodiment has a porosity of 31%, a pore size of 80 μm, a hydrogen content of 0.01 wt.%, and a compressive strength of 220 MPa.
[0089] Example 3
[0090] A method for recycling titanium waste to prepare a high-performance surface-modified titanium filter, the method for recycling titanium waste to prepare a high-performance surface-modified titanium filter comprises the following steps:
[0091] S1. Hydrogenation of titanium raw materials: 100 kg of sponge titanium blocks were hydrogenated in a hydrogenation furnace at a temperature of 320° C. The hydrogen was introduced for 2 h. The hydrogen content of the easily broken titanium hydride blocks was 2.7 wt.%, and easily broken titanium hydride blocks were obtained.
[0092] S2. Preparation of micron-sized titanium hydride powder: The easily broken titanium hydride block of S1 was placed in a ball milling jar filled with high-purity argon gas for high-energy ball milling. The ball-to-material ratio of the high-energy ball milling was 10:1, the ball milling speed was 400 rpm, the grinding balls were stainless steel balls with a size of 8 mm, the ball milling time was 2 h, and 1 wt.% of NaCl pore-forming agent was added during the ball milling to obtain micron-sized titanium hydride powder. The particle size of the micron-sized titanium hydride powder was 200 meshes, and the shape was irregular blocks.
[0093] S3. Preparation of cold forming mold for porous titanium filter: a square tubular soft bag is made of polyurethane, with a stainless steel core rod in the middle of the soft bag, the core rod is fixed by a polyurethane plug matched with the tenon of the upper and lower ports of the soft bag, and a porous stainless steel bushing is matched with the outside of the polyurethane soft bag. The length of the bushing is consistent with the length of the soft bag, and the diameter of the bushing is larger than the diameter of the soft bag. The cold forming mold is composed of the soft bag, the core rod, the plug and the bushing;
[0094] Among them, the total length of the soft bag is 50cm, the inner side length is 60mm, and the thickness is 10mm. The lower end of the soft bag structure is a whole mold and cannot be opened, while the upper end is a split mold and can be partially opened through serrated or corrugated meshing. The length of the upper end is 5 / 8 of the total length of the bag; the stainless steel bushing is a left and right split mold structure, fixed with a throat clamp or buckle; the side length of the mandrel is 39mm, the taper of the mandrel is 3°, the length of the bushing is 50cm, the diameter of the bushing is 82mm, the diameter of the bushing is 15mm, and the hole area is 60% of the total area of the bushing;
[0095] S4, preparation of titanium filter blank: S2 micron-grade alloy powder is loaded into the square tubular soft package in S3, and sealed and assembled; then the forming mold filled with powder is placed in a cold isostatic press for cold isostatic pressing, the pressing pressure of the cold isostatic pressing is 100 MPa, the pressure is maintained for 150 seconds, and the mold is removed to obtain a porous square tubular titanium filter blank; the porous square tubular titanium filter blank has a wall thickness of 10 mm and a porosity of 37%;
[0096] S5. Preparation of porous titanium filter: Place the S4 square tubular titanium filter compact into a vacuum sintering furnace, evacuate and heat to sinter. The vacuum sintering temperature is 1200°C and the vacuum degree is 10 -2 Pa, sintering time is 2h, and porous titanium filter is obtained;
[0097] The porous filter has a porosity of 35%, a pore size of 90 μm, a hydrogen content of 0.01 wt.%, and a compressive strength of 170 MPa;
[0098] S6. Surface modification of porous titanium filter: The S5 porous filter was subjected to surface modification by passing methane gas. The surface modification temperature was 900°C, the insulation time was 2h, the TiC coating thickness was 1mm, and after cooling, a high-performance porous titanium filter with a porous coating on the surface was obtained.
[0099] The high-performance porous titanium filter with a porous coating on the surface prepared in this embodiment has a porosity of 35%, a pore size of 90 μm, a hydrogen content of 0.01 wt.%, and a compressive strength of 220 MPa.
[0100] Example 4
[0101] A method for recycling titanium waste to prepare a high-performance surface-modified titanium filter, the method for recycling titanium waste to prepare a high-performance surface-modified titanium filter comprises the following steps:
[0102] S1. Hydrogenation of titanium raw materials: A 50 kg titanium block is subjected to hydrogenation treatment in a hydrogenation furnace. The temperature of the hydrogenation treatment is 350° C. The hydrogen is introduced and kept warm for 2 hours. The hydrogen content in the easily broken titanium hydride block is 3.2 wt.%, and an easily broken titanium hydride block is obtained.
[0103] S2. Preparation of micron-sized titanium hydride powder: The easily broken titanium hydride block of S1 was placed in a ball milling jar filled with high-purity argon gas for high-energy ball milling. The ball-to-material ratio of the high-energy ball milling was 5:1, the ball milling speed was 400 rpm, the grinding balls were stainless steel balls with a size of 8 mm, the ball milling time was 2 h, and 5 wt.% of NaCl pore-forming agent was added during the ball milling to obtain micron-sized titanium hydride powder. The particle size of the micron-sized titanium hydride powder was 150 meshes, and the shape was irregular blocks.
[0104] S3. Preparation of cold forming mold for porous titanium filter: a tubular soft bag is made of polyurethane, with a stainless steel core rod in the middle of the soft bag, the core rod is fixed by a polyurethane plug matched with the tenon of the upper and lower ports of the soft bag, the polyurethane soft bag is matched with a porous stainless steel bushing, the length of the bushing is consistent with the length of the soft bag, and the diameter of the bushing is larger than the diameter of the soft bag, and the cold forming mold is composed of the soft bag, the core rod, the plug and the bushing;
[0105] Among them, the total length of the soft bag is 100cm, the inner diameter is 60mm, and the thickness is 10mm. The lower end of the soft bag structure is a whole mold and cannot be opened, while the upper end is a split mold and can be partially opened through serrated or corrugated meshing. The length of the upper end is 5 / 8 of the total length of the bag; the stainless steel bushing is a left and right split mold structure, fixed with a throat clamp or buckle; the core rod diameter is 38mm, the core rod taper is 1°, the bushing length is 1000cm, the bushing diameter is 82mm, the bushing aperture is 3mm, and the hole area is 60% of the total bushing area;
[0106] S4, titanium filter blank preparation: S2 micron-grade alloy powder is loaded into the tubular soft package in S3, and sealed and assembled; then the forming mold filled with powder is placed in a cold isostatic press for cold isostatic pressing, the pressing pressure of the cold isostatic pressing is 140MPa, the pressure is maintained for 120s, and the mold is removed to obtain a porous tubular titanium filter blank; the porous tubular titanium filter blank has a wall thickness of 10mm and a porosity of 39%;
[0107] S5. Preparation of porous titanium filter: Place the S4 tubular titanium filter blank into a vacuum sintering furnace, evacuate and heat to sinter. The vacuum sintering temperature is 950°C and the vacuum degree is 10 -2 Pa, sintering time is 2h, and porous titanium filter is obtained;
[0108] The porous filter has a porosity of 37%, a pore size of 70 μm, a hydrogen content of 0.01 wt.%, and a compressive strength of 190 MPa;
[0109] S6. Surface modification of porous titanium filter: nitrogen gas was introduced into the S5 porous filter for surface modification. The surface modification temperature was 850°C, the insulation time was 2h, the TiN coating thickness was 2mm, and after cooling, a high-performance porous titanium filter with a porous coating on the surface was obtained.
[0110] The high-performance porous titanium filter with a porous coating on the surface prepared in this embodiment has a porosity of 37%, a pore size of 70 μm, a hydrogen content of 0.01 wt.%, and a compressive strength of 280 MPa.
[0111] Example 5
[0112] A method for recycling titanium waste to prepare a high-performance surface-modified titanium filter, the method for recycling titanium waste to prepare a high-performance surface-modified titanium filter comprises the following steps:
[0113] S1. Hydrogenation of titanium raw materials: 80 kg of titanium chips without oil on the surface were hydrogenated in a hydrogenation furnace. The temperature of the hydrogenation was 320° C. The hydrogen was introduced for 2 h. The hydrogen content in the easily broken titanium hydride block was 3 wt.%, and an easily broken titanium hydride block was obtained.
[0114] S2. Preparation of micron-sized titanium hydride powder: The easily broken titanium hydride block of S1 was placed in a ball milling jar filled with high-purity argon gas for high-energy ball milling. The ball-to-material ratio of the high-energy ball milling was 5:1, the ball milling speed was 400 rpm, the grinding balls were stainless steel balls with a size of 10 mm, the ball milling time was 2 h, and 5 wt.% of KCl pore-forming agent was added during the ball milling to obtain micron-sized titanium hydride powder. The particle size of the micron-sized titanium hydride powder was 200 meshes, and the shape was irregular blocks.
[0115] S3. Preparation of cold forming mold for porous titanium filter: a tubular soft bag is made of polyurethane, with a stainless steel core rod in the middle of the soft bag, the core rod is fixed by a polyurethane plug matched with the tenon of the upper and lower ports of the soft bag, the polyurethane soft bag is matched with a porous stainless steel bushing, the length of the bushing is consistent with the length of the soft bag, and the diameter of the bushing is larger than the diameter of the soft bag, and the cold forming mold is composed of the soft bag, the core rod, the plug and the bushing;
[0116] Among them, the total length of the soft bag is 90cm, the inner diameter is 120mm, and the thickness is 15mm. The lower end of the soft bag structure is a whole mold and cannot be opened, while the upper end is a split mold and can be partially opened through serrated or corrugated meshing. The length of the upper end is 1 / 2 of the total length of the bag; the stainless steel bushing is a left and right split mold structure, fixed with a throat clamp or buckle; the core rod diameter is 88mm, the core rod taper is 2°, the bushing length is 90cm, the bushing diameter is 152mm, the bushing aperture is 5mm, and the hole area is 50% of the total bushing area;
[0117] S4, titanium filter blank preparation: S2 micron-grade alloy powder is loaded into the tubular soft package in S3, and sealed and assembled; then the forming mold filled with powder is placed in a cold isostatic press for cold isostatic pressing, the pressing pressure of the cold isostatic pressing is 120MPa, the pressure is maintained for 120s, and the mold is removed to obtain a porous tubular titanium filter blank; the porous tubular titanium filter blank has a wall thickness of 15mm and a porosity of 36%;
[0118] S5. Preparation of porous titanium filter: Place the S4 tubular titanium filter blank into a vacuum sintering furnace, evacuate and heat to sinter. The vacuum sintering temperature is 1100°C and the vacuum degree is 10 -2 Pa, sintering time is 2h, and porous titanium filter is obtained;
[0119] The porous filter has a porosity of 34%, a pore size of 60 μm, a hydrogen content of 0.01 wt.%, and a compressive strength of 180 MPa;
[0120] S6. Surface modification of porous titanium filter: methane gas was introduced into the S5 porous filter for surface modification. The surface modification temperature was 900°C, the insulation time was 1 hour, the TiC coating thickness was 2 mm, and after cooling, a high-performance porous titanium filter with a porous coating on the surface was obtained.
[0121] The high-performance porous titanium filter with a porous coating on the surface prepared in this embodiment has a porosity of 34%, a pore size of 60 μm, a hydrogen content of 0.01 wt.%, and a compressive strength of 280 MPa.
[0122] Example 6
[0123] A method for recycling titanium waste to prepare a high-performance surface-modified titanium filter, the method for recycling titanium waste to prepare a high-performance surface-modified titanium filter comprises the following steps:
[0124] S1. Hydrogenation of titanium raw materials: 120 kg of sponge titanium blocks were hydrogenated in a hydrogenation furnace at a temperature of 350° C. The hydrogen was introduced for 2 h. The hydrogen content of the easily broken titanium hydride blocks was 3.1 wt.%, and easily broken titanium hydride blocks were obtained.
[0125] S2. Preparation of micron-sized titanium hydride powder: The easily broken titanium hydride block of S1 was placed in a ball milling jar filled with high-purity argon gas for high-energy ball milling. The ball-to-material ratio of the high-energy ball milling was 10:1, the ball milling speed was 500 rpm, the grinding balls were stainless steel balls with a size of 10 mm, the ball milling time was 2 h, and 1 wt.% of CaCl2 pore-forming agent was added during the ball milling to obtain micron-sized titanium hydride powder. The particle size of the micron-sized titanium hydride powder was 200 meshes, and the shape was irregular blocks.
[0126] S3. Preparation of cold forming mold for porous titanium filter: a square tubular soft bag is made of polyurethane, with a stainless steel core rod in the middle of the soft bag, the core rod is fixed by a polyurethane plug matched with the tenon of the upper and lower ports of the soft bag, and a porous stainless steel bushing is matched with the outside of the polyurethane soft bag. The length of the bushing is consistent with the length of the soft bag, and the diameter of the bushing is larger than the diameter of the soft bag. The cold forming mold is composed of the soft bag, the core rod, the plug and the bushing;
[0127] Among them, the total length of the soft bag is 200cm, the inner side length is 100mm, and the thickness is 15mm. The lower end of the soft bag structure is a whole mold and cannot be opened, while the upper end is a split mold and can be partially opened through serrated or corrugated meshing. The length of the upper end is 1 / 4 of the total length of the bag; the stainless steel bushing is a left and right split mold structure, fixed with a throat clamp or buckle; the side length of the mandrel is 68mm, the taper of the mandrel is 3°, the length of the bushing is 200cm, the diameter of the bushing is 136mm, the diameter of the bushing is 15mm, and the hole area is 70% of the total area of the bushing;
[0128] S4, preparation of titanium filter blank: S2 micron-grade alloy powder is loaded into the square tubular soft package in S3, and sealed and assembled; then the forming mold filled with powder is placed in a cold isostatic press for cold isostatic pressing, the pressing pressure of the cold isostatic pressing is 120MPa, the pressure is maintained for 150s, and the mold is removed to obtain a porous square tubular titanium filter blank; the porous square tubular titanium filter blank has a wall thickness of 15mm and a porosity of 34%;
[0129] S5. Preparation of porous titanium filter: Place the S4 square tubular titanium filter compact into a vacuum sintering furnace, evacuate and heat to sinter. The vacuum sintering temperature is 1200°C and the vacuum degree is 10 -2 Pa, sintering time is 2h, and porous titanium filter is obtained;
[0130] The porous filter has a porosity of 30%, a pore size of 40 μm, a hydrogen content of 0.01 wt.%, and a compressive strength of 180 MPa;
[0131] S6. Surface modification of porous titanium filter: The S5 porous filter was subjected to surface modification by passing methane gas. The surface modification temperature was 900°C, the insulation time was 2h, the TiC coating thickness was 2mm, and after cooling, a high-performance porous titanium filter with a porous coating on the surface was obtained.
[0132] The high-performance porous titanium filter with a porous coating on the surface prepared in this embodiment has a porosity of 30%, a pore size of 40 μm, a hydrogen content of 0.01 wt.%, and a compressive strength of 290 MPa.
[0133] The above scheme proposes a method for recycling titanium waste to prepare a high-performance surface-modified titanium filter, which can solve the problems of the titanium filter currently used in titanium tetrachloride in the prior art, such as short service life, insufficient filtration accuracy, complex process flow, easy clogging of pores, uneven pore distribution, poor high temperature resistance and corrosion resistance, high preparation cost, poor filtration efficiency, large urea loss and poor pore opening effect, insufficient tight bonding between nano-TiN ceramic particles and titanium alloy matrix, uneven distribution of nano-TiN particles, difficulty in simultaneously controlling the size, distribution and shape of pores, interaction between pores and particles, high temperature may cause further weakening of interface bonding force, or adverse chemical reactions between particles and matrix.
[0134] The present invention uses incompletely hydrogenated titanium hydride as a raw material to prepare a porous titanium filter. During the sintering process, the titanium hydride undergoes a dehydrogenation reaction to achieve dehydrogenation and sintering integration, and the hydrogen gas released at high temperature serves to form pores. After sintering, the hydrogen content is ≤0.03wt.%, shortening the production process and reducing the production cost.
[0135] The present invention adopts mold design and preparation, cold isostatic pressing process, can realize near-forming of the filter, thereby reducing the preparation cost of the filter. In particular, the specification and shape of the cold isostatic pressing package can be designed to prepare filters required by different application scenarios.
[0136] The hydrogenated powder used in the present invention has a particle size of 50-200 meshes, which avoids the problem that when the powder particle size is small, the relative density of the pressed green sheet is large and it is difficult to ensure the porosity of the filter, and also avoids the problems that when the powder particle size is large, the filter strength is low, slag is easy to fall off, and the service life is short.
[0137] The present invention generates TiC or TiN strengthening coatings in situ on the inner and outer surfaces of the porous titanium filter through surface modification treatment with nitrogen or methane gas, which will not affect the porosity of the filter. At the same time, the porous titanium filter can have the advantages of high wear resistance, high hardness, high corrosion resistance and the like of TiC or TiN, thereby greatly improving the service life of the filter.
[0138] The application of the cold isostatic pressing process of the present invention also effectively improves the yield rate of the titanium filter, and the material utilization rate is ≥98%. In addition, the use of off-grade titanium as a raw material further reduces the production cost. The filter prepared by the present invention can achieve a significant improvement in the purification efficiency of titanium tetrachloride, providing a more economical and efficient solution for the recycling and production of titanium resources.
[0139] In summary, compared with other traditional methods, the method of the present invention uses off-grade titanium and other titanium waste materials with no oil on the surface, such as titanium chips, scraps, etc. as raw materials, and adopts hydrogenation crushing, cold forming, sintering, surface modification and other processes to prepare high-performance titanium filters, which have long service life, high filtration accuracy, short production process and low production cost; and solves the problems of short service life, easy perforation, easy breakage, insufficient filtration accuracy and high cost of the existing filters used to filter titanium tetrachloride. The filter preparation technology involved in the present invention has no special restrictions on the raw material composition, can meet the needs of different production environments and conditions, and has wide applicability.
[0140] It should be understood that the term "and / or" in this article is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship, but it may also indicate an "and / or" relationship. Please refer to the context for specific understanding.
[0141] In the present invention, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, at least one of a, b, or c can mean: a, b, c, ab, ac, bc, or abc, where a, b, and c can be single or multiple.
[0142] It should be understood that in various embodiments of the present invention, the size of the serial numbers of the above-mentioned processes does not mean the order of execution. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present invention.
[0143] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for recycling titanium waste to prepare high-performance surface-modified titanium filters, characterized in that: The method for recycling titanium waste to prepare a high-performance surface-modified titanium filter comprises the following steps: S1. hydrogenation of titanium raw material: hydrogenation treatment is performed on titanium raw material block by using hydrogenation furnace to obtain easily breakable hydrogenated titanium block; S2. Preparation of micron-sized titanium hydride powder: The easily broken titanium hydride block in S1 is placed in a ball mill filled with high-purity argon gas for high-energy ball milling, and a pore-forming agent is added during ball milling to obtain micron-sized titanium hydride powder; S3. Preparation of cold forming mold for porous titanium filter: a tubular or square tubular soft sleeve is made of polyurethane or silicone, with a stainless steel core rod in the middle of the soft sleeve, which is fixed by a polyurethane or silicone plug matched with the tenon of the upper and lower ports of the soft sleeve, and a porous stainless steel bushing is matched with the outside of the polyurethane or silicone soft sleeve, the length of the bushing is consistent with the length of the soft sleeve, and the diameter of the bushing is larger than the diameter of the soft sleeve, and the cold forming mold is composed of the soft sleeve, the core rod, the plug and the bushing; S4, preparation of porous titanium filter compact: loading the micron-grade titanium hydride powder of S2 into the tubular or square tubular soft package in S3, and performing sealing and assembly treatment; then placing the forming mold filled with the powder into a cold isostatic press for cold isostatic pressing, demolding and taking out, to obtain a tubular or square tubular porous titanium filter compact; S5. Preparation of porous titanium filter: placing the S4 tubular or square tubular titanium filter compact into a vacuum sintering furnace, evacuating the vacuum furnace and heating and sintering the compact to obtain a porous titanium filter; S6. Surface modification of porous titanium filter: nitrogen or methane gas is passed into the S5 porous filter for surface modification to obtain a high-performance porous titanium filter with a porous coating on the surface.
2. The method for preparing high-performance surface-modified titanium filters by recycling titanium waste according to claim 1, characterized in that: The temperature of hydrogenation treatment in S1 is 300-600°C, the holding time is 1-4h, the hydrogen content in the easily broken hydrogenated titanium block is 2-3.2wt.%, and the titanium raw material block is off-grade titanium, sponge titanium or other titanium waste with no oil on the surface.
3. The method for preparing high-performance surface-modified titanium filter by recycling titanium waste according to claim 1, characterized in that: The pore-forming agent in S2 is NaCl, KCl or CaCl2 salt, and the addition amount is 1-5wt.%; the ball-to-material ratio of high-energy ball milling is 5:1-10:1, the ball milling speed is 300-600rpm, the grinding balls are stainless steel balls with a diameter of 6-10mm, the ball milling time is 2-4h, the particle size of micron-sized titanium hydride powder is 50-200 mesh, and the shape is irregular block.
4. The method for preparing high-performance surface-modified titanium filter by recycling titanium waste according to claim 1, characterized in that: The total length of the soft bag in S3 is 5-200cm, and the thickness is 5-25mm. The lower end of the soft bag structure is a whole mold and cannot be opened, while the upper end is a split mold and is partially opened through serrated or corrugated meshing. The length of the upper end is 1 / 2-3 / 4 of the total length of the bag; the stainless steel bushing is a left and right split mold structure, fixed with a throat clamp or a buckle, and the bushing thickness is 1-3mm; the core rod taper is 1-3°, and the bushing diameter is 2-8mm larger than the diameter of the soft bag; the hole diameter of the porous stainless steel bushing is 3-20mm, and the hole area is 50-80% of the outer surface area of the bushing.
5. The method for preparing high-performance surface-modified titanium filter by recycling titanium waste according to claim 1, characterized in that: The pressing pressure of S4 cold isostatic pressing is 80-200MPa, the pressure holding time is 60-240s, the wall thickness of the tubular or square tubular titanium filter blank is 10-20mm, and the porosity is 30-55%.
6. The method for preparing high-performance surface-modified titanium filter by recycling titanium waste according to claim 1, characterized in that: The vacuum sintering temperature in S5 is 950-1200℃ and the vacuum degree is 10 -2 Pa, sintering time is 1-4h.
7. The method for preparing high-performance surface-modified titanium filter by recycling titanium waste according to claim 1, characterized in that: The high-performance porous titanium filter in S5 has a porosity of 30-60%, a pore size of 10-100μm, a hydrogen content of ≤0.03wt.%, and a compressive strength of ≥150MPa.
8. The method for preparing high-performance surface-modified titanium filter by recycling titanium waste according to claim 1, characterized in that: The temperature of the surface modification treatment in S6 is 750-1000°C, and the holding time is 1-2h.
9. The method for preparing high-performance surface-modified titanium filter by recycling titanium waste according to claim 1, characterized in that: The inner and outer walls of the S6 medium and high performance porous titanium filter with porous coating on the surface are both porous coatings of TiN or TiC, with a coating thickness of 1-3mm, a porosity of 30-60%, a pore size of 10-100μm, a hydrogen content of ≤0.03wt.%, and a compressive strength of ≥200MPa.
Citation Information
Patent Citations
Preparing method of in-situ synthesis titanium carbide enhanced titanium-based multi-hole materials
CN104141063A
Preparation method of titanium-based porous composite containing nanometer TiN ceramic
CN107287464A
Method for preparing TiCN coating layer in situ on surface of titanium alloy
CN108251789A
Porous membrane with TiN coating and preparation method thereof
CN102719691A
Low-cost method for industrially producing TiC particle reinforced titanium-based composite material
CN108193064A